New challenges for intelligent information and database systems - #aNguyen, Ngoc Thanh (Computer scientist).; Trawiński, Bogdan; Jung, Jason J.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
The book consists of 35 extended chapters which have been based on selected submissions to the poster session organized during the 3rd Asian Conference on Intelligent Information and Database Systems (20-22 April 2011 in Daegu, Korea). The book is organized into four parts, which are information retrieval and management, data mining and computational intelligence, service composition and user-centered approach, and intelligent management and e-business, respectively. All chapters in the book discuss theoretical and practical issues related to integration of artificial intelligence and database technologies in order to develop various intelligent information systems in many different domains. Such combination of artificial intelligence and database technologies has been regarded as one of the important interdisciplinary subfields of modern computer science, due to the sustainable development of networked information systems. Especially, service-oriented architecture and global multimedia systems used on a number of different purpose call for these developments. The book will be of interest to postgraduate students, professors and practitioners in the areas of artificial intelligence and database systems to modern information environments. The editors hope that readers of this volume can find many inspiring ideas and influential practical examples and use them in their future work.
Part I: Information Retrieval and Management -- Part II: Data Mining and Computational Intelligence -- Part III: Service Composition and User-Centered Approach -- Part IV: Intelligent Management and e-Business.
Electronic reproduction.
Keywords: Expert systems (Computer science); Database management; Electronic books